An osteosclerotic form of Robinow syndrome. Issue 10 (14th July 2014) - Bunn, Kieran J.; Lai, Angeline; Al‐Ani, Azza; Farella, Mauro; Craw, Susan; Robertson, Stephen P.
Abstract: Robinow syndrome (RS) is a clinically and genetically heterogenous condition primarily characterized by short stature, mesomelia, genital hypoplasia, oral abnormalities, and a facial gestalt that includes hypertelorism, a short nose, and a broad mouth. The disorder exists in both a dominant and a more severe recessive form. Here two unrelated cases of sporadic RS are described with the additional finding of axial and appendicular osteosclerosis. These two patients, coupled with three additional patients previously described in the literature, may represent a distinct sub‐phenotype of this condition. © 2014 Wiley Periodicals, Inc.